Isolation of acid tolerant lactic acid bacteria and evaluation of α-glucosidase inhibitory activity - Kwun, Se Young; Bae, Young Woo; Yoon, Jeong Ah; Park, Eun Hee; Kim, Myoung Dong (Food science and biotechnology, 2020)
In this study, lactic acid bacteria strains (LABs) were isolated from Korean traditional fermented food and examined as potential probiotics using in vitro methods. Ten LAB strains survived in de Man, Rogosa and Sharpe broth adjusted to pH 2.5 were tested for resistance to acidic conditions and bile, antimicrobial activity, and α-glucosidase inhibitory activity. Among them, strain MBEL1397 showed antimicrobial activity against Bacillus cereus and exhibited survival rates of over 97% in acidic and bile conditions. The α-glucosidase inhibitory activity was 3.91 ± 0.25%, corresponding to approximately 2.3 times higher than that of acarbose. MBEL1397 was susceptible to ampicillin, erythromycin, and penicillin G and identified as Lactobacillus sakei. It was deposited to Korean Collection for Type Culture (KCTC) as KCTC14037BP. In conclusion, these results demonstrate that L. sakei MBEL1397 might be prominent probiotics with potential hypoglycemic effects.